Induction of apoptosis by Eleutherine bulbosa (Mill.) Urb. bulb extracted under optimised extraction condition on human retinoblastoma cancer cells (WERI-Rb-1) - Kamarudin, Ammar Akram; Sayuti, Nor Hafiza; Saad, Norazalina; Ab Razak, Nor Asma; Mohd Esa, Norhaizan (Elsevier, 2022)
Ethnopharmacological relevance: The bulb of Eleutherine bulbosa (Mill.) Urb. is an indigenous medicinal plant traditionally used among Dayak people for the management of diabetes, breast cancer, hypertension, stroke, and fertility problems in women. The bulb has been reported with a potent cytotoxic potential but with limited underlying mechanisms. Aim of the study: This study aimed to investigate the cytotoxic properties of E. bulbosa ethanolic bulb extracted under optimised extraction condition on retinoblastoma cancer cells (WERI-Rb-1) through in vitro cell culture bioassays. The optimised extraction condition has been determined in the previous reports. Materials and methods: Cytotoxic assay was analysed through MTT assay. Comparison between non-optimised and optimised extraction condition from E. bulbosa ethanolic bulb extract was evaluated. Morphological assessment of apoptotic cells was conducted through acridine orange propidium iodide (AOPI) staining using fluorescence microscopy. Apoptosis assay was carried out through Annexin V-FITC and cell cycle analysis through PI staining. The effect of varying concentrations (IC25, IC50, IC75) of the optimised E. bulbosa ethanolic bulb extract was observed. The mRNA expression was also conducted to confirm the underlying mechanism. Results: The optimised E. bulbosa ethanolic bulb extract markedly suppressed the proliferation of retinoblastoma cancer cells significantly with an IC50 value of 15.7 μg/mL as compared to non-optimised extract (p < 0.01). Fluorescence microscopy revealed that retinoblastoma cancer cells manifested early features of apoptosis-like membrane blebbing, chromatin condensation and formation of apoptotic bodies in a dose-dependent manner. The number of apoptotic cells were greatly observed in early and late apoptosis through Annexin V-FITC and the extract also induced cell arrestment as compared to the untreated group. The apoptosis was confirmed with the upregulation of Bax, Bad, p53, Caspase 3, Caspase 8, and Caspase 9 genes meanwhile, Bcl-2, BcL-xL, Nrf-2, and HO-1 genes were downregulated. Conclusion: The optimised E. bulbosa ethanolic bulb extract induced a significant cell death and cell cycle arrestment on retinoblastoma cancer cells. It could be suggested that the induction of apoptosis in retinoblastoma cancer cells may be due to the synergistic effect of the bioactive compounds extracted under optimised extraction condition. Our findings indicated that E. bulbosa bulb could be promising chemotherapeutic potential to treat retinoblastoma cancer cells.